Introduction to Batak Culture through Ulos as an Idea for Creation of Collage Painting Techniques - Nabila Priska Stania; Mukhriza Pratama; Adek Cerah Kurnia Azis; Ayu Astiani; Anisa Indriyanti; Veronica Br Panjaitan (Gorga : Jurnal Seni Rupa, 2026)
North Sumatra, as a metropolitan province on the island of Sumatra, has a diverse cultural wealth, one of which is Ulos, which is an important identity of the Batak Toba people and needs to be preserved to remain relevant amidst the development of the times. This creative research aims to maintain the cultural value of Ulos through visual exploration in collage painting works. The objectives of the research include: identifying and formulating designs for Ulos-themed works that maintain the authenticity of cultural values; explaining the process and techniques of creating paintings with the concept of Ulos as a form of cultural preservation; and evaluating the final results of the work from an aesthetic aspect. The method used is the I Made Bandem creative method, which includes five stages: preparation, elaboration, synthesis, concept realization, and completion. Through this method, the research produces collage paintings that combine elements of tradition and contemporary visual approaches, thus presenting novelty in the presentation of Ulos motifs as an expression of cultural preservation. The findings show that the collage technique is able to strengthen the texture, pattern, and symbolic character of Ulos in the painting medium, as well as providing an innovative alternative for efforts to strengthen Batak cultural identity through fine art. This research confirms that collage painting can be an effective means of maintaining and developing local cultural heritage.